Experimental Investigation of the Effect of Implanting TiO(2)-NPs on PVC for Long-Term UF Membrane Performance to Treat Refinery Wastewater - Al-Ani, Faris H. (Membranes (Basel), 2020)
This study investigated the impact of implanting TiO(2)-NPs within a membrane to minimize the influence of long-term operation on the membrane characteristics. Four poly vinyle chloride-titanium oxide (PVC-TiO(2)-NPs) membranes were prepared to create an ultrafiltration membrane (UF) that would effectively treat actual refinery wastewater. The hypothesis of this work was that TiO(2)-NPs would function as a hydrophilic modification of the PVC membrane and excellent self-cleaning material, which in turn would greatly extend the membrane’s lifetime. The membranes were characterized via Fourier transforms infrared spectroscopy (FTIR), X-ray diffraction (XRD), energy dispersive X-ray (EDX), atomic force microscope (AFM), and scanning electron microscope (SEM). The removal efficiency of turbidity, total suspended solid (TSS), oil and grease, heavy metals and chemical oxygen demand (COD) were investigated. Contact angle (CA) reduced by 12.7% and 27.5% on the top and bottom surfaces, respectively. The PVC membrane with TiO(2)-NPs had larger mean pore size on its surface and more holes with larger size inside the membrane structure. The addition of TiO(2)-NPs could remarkably enhance the antifouling property of the PVC membrane. The pure water permeability (PWP) of the membrane was enhanced by 95.3% with an increase of TiO(2) to 1.5 gm/100gm. The PWP after backwashing was reduced from 22.3% for PVC to 10.1% with 1.5 gm TiO(2)-NPs. The long-term performance was improved from five days for PVC to 23 d with an increase in TiO(2)-NPs to 1.5 gm. The improvements of PVC-TiO(2)-NPs long-term were related to the enhancement of the hydrophilic character of the membrane and increase tensile strength due to the reinforcement effect of TiO(2)-NPs. These results clearly identify the impact of the TiO(2)-NPs content on the long-term PVC/TiO(2)-NPs performance and confirm our hypothesis that it is possible to use TiO(2)-NPs to effectively enhance the lifetime of membranes during their long-term operation.